Menyelami lautan jilbab: Antara spiritualitas dan gaya modis perempuan muslim di era modern - Nisa', Khoirun (Maliki Interdisciplinary Journal, 2026)
This article explores the complex dynamics surrounding the hijab in the modern era, where spirituality, identity, and fashion trends intersect. The hijab functions not only as a symbol of obedience and spiritual devotion for Muslim women but also as part of cultural expression shaped by the growth of the modest fashion industry. Technological advancement and the dominance of social media have transformed how women interpret and display their hijab, giving rise to the phenomenon of “algorithmic piety,” in which aesthetics and public validation significantly influence religious expression. At the same time, cultural acculturation such as the integration of local motifs like batik demonstrates that the hijab serves as a creative medium that enriches Indonesian Muslim women’s identity. However, the commodification of the hijab and its reduction to a mere fashion trend risk diminishing its spiritual meaning. This study concludes that the ideal understanding of the hijab must balance outward aesthetics and inner spirituality, ensuring that the practice of wearing the hijab remains grounded in sincerity amid the pressures of modernity.